Psammoma bodies as signs of choroid plexus ageing – a morphometric analysis - Živković, Vladimir S.; Stanojković, Milica M.; Antić, Milorad M. (Vojnosanitetski pregled, 2017)
Background/Aim. Psammoma bodies (PB) are regarded as benign consequences of ageing in choroid plexus stroma. The aim of this study was to assess the morphometric characteristics of psammoma bodies of all four choroid plexuses during the ageing process. Our intention was to find the possible relations between psammoma bodies and choroid plexus and blood vessels parameters. Methods. This study was conducted on the material taken from 15 cadavers during routine autopsies. Tissue samples were collected from both lateral, third and forth ventricles’ choroid plexus. Slices were stained with Mallory trichrome stains. In each image, we analyzed morphometrically the epithelium, blood vessels present and all the psammoma bodies. Results. With age, right choroid plexus surface density decreases (p < 0.05), while the psammoma bodies volume density increases (p < 0.05). A decrease in the blood vessels volume density was observed in the third ventricle’s choroid plexus (p < 0.05), as well as an age-related decrease in the psammoma bodies perimeter (p < 0.01). Not associated with ageing, the increase in psammoma bodies perimeter and volume density predicts a decrease in choroid plexus surface density (p < 0.05 and p < 0.001, respectively). There was a decrease in the volume density of blood vessels with age and with the increase in Feret’s diameter of psammoma bodies, (p < 0.001 and p < 0.05, respectively). Conclusion. We want to point out that there is an association between ageing and increased size and volume density of psammoma bodies. More important is the fact that psammoma bodies’ presence and their morphometric characteristics are good predictors of changes occurring on the level of choroid plexus structure and vascularization, which may have crucial effects on the choroid plexus physiology